1981
DOI: 10.3147/jsfp.15.319
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Activities of Aeromonas hydrophila biovar hydrophila (Chester) POPOFF and VERON, 1976 to Fishes

Abstract: A total 291 strains of motile members of the genus Aeromonas were classified according to the taxonomic scheme proposed by POPOFF and VERON (1976). Forty three were indetified as A. hydrophila biovar hydrophila, 9 as A. hydrophila biovar anaerogenes, and 52 as A. sobria. The remaining 187 strains could not be identified. Thirty seven (86%) of 43 A. hydrophila biovar hydrophila, 3 (33 %) of 9 A. hydrophila biovar anaerogenes, 32 (62 %) of 52 A. sobria, and 65 (35%) of the 187 unidentified originated from fishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 13 publications
1
26
0
1
Order By: Relevance
“…Recent studies (WAKABAYASHI et al, 1981;HSU et al, 1981) have demonstrated that the proteolytic activity of elastase and caseinase are associated with the virulence of A. hydrophila complex strains. Several extensive reports dealing with Pseudomonas aeruginosa indicate that these proteases could also be virulence factors of that organism (HOLDER and HAIDARIS, 1979;JANDA and BOTTONE, 1981;PAVLOVSKIS and WRETLIND, 1979;SNELL et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (WAKABAYASHI et al, 1981;HSU et al, 1981) have demonstrated that the proteolytic activity of elastase and caseinase are associated with the virulence of A. hydrophila complex strains. Several extensive reports dealing with Pseudomonas aeruginosa indicate that these proteases could also be virulence factors of that organism (HOLDER and HAIDARIS, 1979;JANDA and BOTTONE, 1981;PAVLOVSKIS and WRETLIND, 1979;SNELL et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…However, strain diversity within Aer. hydrophila is well known ( Wakabayashi et al . 1981 ; Nieto and Ellis 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, strain diversity within Aer. hydrophila is well known (Wakabayashi et al 1981;Nieto and Ellis 1991). This diversity has previously been used to explain the differences in genotypic and phenotypic characteristics observed in Aer.…”
Section: E N Z Y M E E X P R E S S I O N I N a E R H Y D R O P H I L Amentioning
confidence: 99%
“…Aeromonas hydrophila , an aetiological agent of fish diseases, is considered to be a primary and secondary pathogen resulting in haemorrhagic septicaemia in fish (Lu 1992). It is found usually in freshwater fish species (Wakabayashi, Kanai, Hsu & Egusa 1981) but occasionally in marine fish (Kaper, Lockman, Colwell & Joseph 1981). Edwardsiella tarda causes the serious systemic disease, commonly known as Edwardsiella septicaemia or edwardsiellosis which occurred in cultured Japanese eels ( Anguilla japonica ) in Japan, China and Taiwan (Egusa 1976; Liu & Tsai 1980).…”
Section: Introductionmentioning
confidence: 99%